THE IMPORTANCE OF APPLYING WATER-SAVING TECHNOLOGIES IN MAIZE CULTIVATION - U. S. Saksonov; X. B. Buriev; A. V. Baqoev (Web of Journals Publishing, 2025)
This article presents the results of experiments conducted on the use of drip irrigation as a water-saving technology in maize cultivation.
Keywords: Corn, resource, fertilizer, drip, irrigation, climate, standard, technology.